Game theory and the design of self-configuring, adaptive wirelessnetworks. - MacKenzie, A.B.
Game theory provides a wealth of tools that can be applied to the design and operation of communications systems. In this article, we provide a brief introduction to game theory. We then present applications of game theory to problems in random access and power control. In the case of random access, we examine the behavior of selfish users in a simplified Aloha system; surprisingly, rational selfish users do not implement the ?always transmit? strategy that one might expect. In the case of power control, we show that game theoretic techniques can yield an optimal operating point without the intervention of an external controller
Keywords: Always transmit strategy; Game theory; Optimal operating point; Power control; Random access; Rational selfish users; Self-configuring adaptive wireless networks; Selfish users; Simplified Aloha system